Effect of the Shanghai Stroke Service System (4S) on the quality of stroke care and outcomes: A prospective quality improvement project. Issue 5 (June 2023) - Xu, Jiawen; Xie, Yanan; Fang, Kun; Wang, Xin; Chen, Shengdi; Liu, Xueyuan; Zhao, Yuwu; Guan, Yangtai; Cai, Dingfang; Li, Gang; Liu, Jianmin; Liu, JianRen; et al.
Background: In China, disparities in the quality of stroke care still exist and implementing quality improvement is still a challenge. Aim: The aim of the study was to determine whether the intervention by Shanghai Stroke Service System (4S) has helped improve adherence to stroke care guidelines and patient outcome. Methods: The 4S is a regional stroke network with real-time data extraction among its 61 stroke centers in Shanghai. A total of 11 key performance indicators (KPIs) were evaluated. The primary outcomes were a composite measure and an all-or-none measure of adherence to 11 KPIs. The secondary outcomes were length of hospital stay and in-hospital mortality. Results: The study enrolled 92, 395 patients (mean age 69.0 ± 12.5 years, 65.2% men) with acute ischemic stroke hospitalized within 7 days of onset in Shanghai from January 2015 to December 2020. More patients received guideline recommended care between 2018 and 2020 than those between 2015 and 2017 (composite measure 87.1% vs 83.6%; absolute difference 2.9%, 95% confidence interval (CI) = [2.7%, 3.2%], p < 0.001; all-or-none measure 49.2% vs 44.8% patients; absolute difference 3.5%, 95% CI = [2.7%, 4.2%], p < 0.001). Further analysis of individual KPIs showed an absolute increase in six KPIs ranging from 3.4% to 8.9% (p < 0.001 for all comparisons). Compared with 2015–2017, hospital length of stay was shorter (10.95 vs 11.90 days; absolute difference –1.08, 95% CI = [–1.18, –0.99], p < 0.001), and in-hospital mortality was significantly reduced (risk ratio (RR) = 0.88, 95% CI = [0.79, 0.98], p = 0.01) in 2018–2020. Conclusion: The 4S intervention was associated with increased adherence to the stroke care guidelines, which further translated to improved clinical outcomes. Trial registration: ClinicalTrials.gov identifier: NCT02735226.